Analysis of Employee Performance Through Islamic Work Environment Factors - Zuki Kurniawan (Al-Hayat: Journal of Islamic Education, 2022)
This study aims to determine the conditions of the Islamic work environment and how significant the influence of the Islamic work environment is on the performance of employees at PT Bina Informatika Solusi Cirebon. This research is a type of descriptive research with hypothesis testing. This study's population was all PT Bina Informatika Solusi Cirebon employees, totalling 50. The entire population is taken as a sample, so it is called population research and does not use sampling techniques. The data collection technique uses a questionnaire that has been tested beforehand and tested for validity and reliability. The data analysis technique used is correlation coefficient analysis, determination coefficient test, hypothesis testing, and simple regression testing. The results of this study indicate that there is a significant influence between the work environment system (X) on employee performance (Y) with a regression equation of Y = a + bx or Y = 3.010 + 0.946 x and with a coefficient of determination (r2) of 0.6034 or 60.34%. In comparison, the remaining 39.66% is influenced by other variables not observed in this study and uses the t-test, which yields if t (table) at Î± 0.05 or 5%, it is obtained at 2.009, then t (count ) is higher than t (table), namely 8.59> 2.009. This means that there is a significant influence of the Islamic work environment variable (X) on employee performance (Y) at PT Bina Informatika Solusi Cirebon.